2009
DOI: 10.4021/jocmr2009.07.1252
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde and Antioxidant Enzymes in Maternal and Cord Blood, and their Correlation in Normotensive and Preeclamptic Women

Abstract: BackgroundAn increased oxidative level and decreased antioxidant activities in the blood of preeclamptic women have been reported by us and other workers. The present study was aimed to evaluate oxidative stress in infants born to preeclamptic mothers, and to examine whether cord blood with oxygen radical disease had different total enzymatic antioxidant status than those without preeclampsia.MethodsThe present study consisted of 23 normotensive (served as control) and 23 preeclamptic mothers. We compared thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
4
22
1
3
Order By: Relevance
“…We concluded that the high TAS levels in the cord blood of BBPM indicated an increased antioxidant defense capacity in the blood of the fetus, probably providing protection against the increased oxidative damage in the mother. Our results were similar to those of the studies by Tastekin et al, 31 Suhail et al, 23,30 and Bowen et al 22 Another condition that could affect the oxidative level in the newborn is the maturation of the baby. Indeed, it was claimed that oxidative stress-related diseases are more frequently observed in premature babies than in full-term babies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We concluded that the high TAS levels in the cord blood of BBPM indicated an increased antioxidant defense capacity in the blood of the fetus, probably providing protection against the increased oxidative damage in the mother. Our results were similar to those of the studies by Tastekin et al, 31 Suhail et al, 23,30 and Bowen et al 22 Another condition that could affect the oxidative level in the newborn is the maturation of the baby. Indeed, it was claimed that oxidative stress-related diseases are more frequently observed in premature babies than in full-term babies.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, studies on the oxidant-antioxidant status of the fetus and newborn have reported conflicting results. [21][22][23][24][25][26][27][28][29][30][31][32][33] Mehendale et al 24 showed that malondialdehyde (MDA) levels increased and vitamin C and E levels decreased in both maternal and cord blood, in preeclamptic mothers and BBPM. Howlader et al 26 demonstrated that thiobarbituric acid reactive substance (TBARS) and lipid hydroperoxide levels were higher, but TAS and vitamin C levels were lower in the cord blood of the BBPM group than in the cord blood of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde (MDA) is known as a secondary metabolite that is produced from the lipid peroxidation of cell membrane and the amount of MDA is used as an indicator for lipid peroxidation of cell membrane which could cause cell damage [21]. In contrast, nitric oxide (NO) plays the role as an inflammatory indicator where it would accumulate as the hepatocytes injuries [26].…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde (MDA) formation in the liver, which is a thiobarbituric acid-reactive substance, was measured by lipid peroxidation estimation according to Suhail et al [21] with slight modification. The estimation of MDA level in liver homogenate was performed by mixing 100  μ L of liver homogenate sample with 400  μ L of phosphate-buffered saline, 12.5  μ L of butylated hydroxytoluene (8.8 mg/mL absolute ethanol), and 250  μ L of 30% w/v trichloroacetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…In clinical chemistry and medicine, ions are very important, since they appear as significant biomarkers for various diseases, and the fluctuations of their concentrations reveal the function of organs as well as of the whole metabolism . For example, sodium (Na + ) and potassium (K + ) are both essential elements that occur at high concentrations in the body and they have crucial roles in cellular homeostasis (Na + /K + ATPases) . Magnesium (Mg 2+ ) mainly is distributed in bones, skeletal muscles and soft tissues.…”
Section: Metabolomics and Bioanalytical Chemistry Of Inorganic Ionsmentioning
confidence: 99%